Recent progress in sono-photodynamic cancer therapy: From developed new sensitizers to nanotechnology-based efficacy-enhancing strategies - Yilin Zheng (Acta Pharmaceutica Sinica B, 2021)
Many sensitizers have not only photodynamic effects, but also sonodynamic effects. Therefore, the combination of sonodynamic therapy (SDT) and photodynamic therapy (PDT) using sensitizers for sono-photodynamic therapy (SPDT) provides alternative opportunities for clinical cancer therapy. Although significant advances have been made in synthesizing new sensitizers for SPDT, few of them are successfully applied in clinical settings. The anti-tumor effects of the sensitizers are restricted by the lack of tumor-targeting specificity, incapability in deep intratumoral delivery, and the deteriorating tumor microenvironment. The application of nanotechnology-based drug delivery systems (NDDSs) can solve the above shortcomings, thereby improving the SPDT efficacy. This review summarizes various sensitizers as sono/photosensitizers that can be further used in SPDT, and describes different strategies for enhancing tumor treatment by NDDSs, such as overcoming biological barriers, improving tumor-targeted delivery and intratumoral delivery, providing stimuli-responsive controlled-release characteristics, stimulating anti-tumor immunity, increasing oxygen supply, employing different therapeutic modalities, and combining diagnosis and treatment. The challenges and prospects for further development of intelligent sensitizers and translational NDDSs for SPDT are also discussed.